2013
DOI: 10.1177/0047287513514295
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Destination Advertising

Abstract: Park, Nicolau, and Fesenmaier proposed the Destination Advertising Response (DAR) model as a means to more effectively evaluate destination advertising campaigns by incorporating the key decisions or components (i.e., facets) that comprise a trip. While this model appears to be an attractive alternative to traditional destination advertising evaluation, little research has been conducted to examine its validity. The goal of this study is to evaluate the potential usefulness of the DAR framework based upon curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 48 publications
6
43
0
3
Order By: Relevance
“…Travellers are more likely to decide on their destination in the early stage and then products being consumed at the destination would be determined accordingly (e.g., accommodation, restaurants). Recently, Stienmetz, Maxcy, and Fesenmaier (2013) proposed facet-based advertising model and estimated the effect of travellers' responses to the advertising for each facet on total trip expenditure. However, the model includes lack of concerning the hierarchical process as well as the multi-category decisions.…”
Section: Tourism Advertising Effectivenessmentioning
confidence: 99%
“…Travellers are more likely to decide on their destination in the early stage and then products being consumed at the destination would be determined accordingly (e.g., accommodation, restaurants). Recently, Stienmetz, Maxcy, and Fesenmaier (2013) proposed facet-based advertising model and estimated the effect of travellers' responses to the advertising for each facet on total trip expenditure. However, the model includes lack of concerning the hierarchical process as well as the multi-category decisions.…”
Section: Tourism Advertising Effectivenessmentioning
confidence: 99%
“…Os estudos de conversão analisam as respostas dos indivíduos às campanhas promocionais em termos de sensibilização sobre o destino, a visitação e as despesas dos visitantes (Stienmetz, Maxcy & Fesenmaier, 2015). Pratt et al (2010) mencionam que a grande vantagem das análises de conversão consiste na aplicação e na interpretação simples, tendo em vista que, ao final, os pesquisadores obterão uma riqueza de informações que podem ser de grande utilidade para as DMOs e outras organizações.…”
Section: Eficácia Promocional De Destinos Turísticosunclassified
“…), quanto da viagem (distância, tempo de estada, fins da viagem, etc.). 2015Os dois primeiros estágios do DAR Model seguem as mesmas características do processo sequencial das análises de conversão e de rastreamento publicitário (Stienmetz, Maxcy & Fesenmaier, 2015), em que, primeiramente, o visitante é exposto à informação (publicidade) difundida pela DMO, fazendo com que seja gerada uma atitude em relação a isto. Posteriormente, a atitude em relação à publicidade influenciará na atitude em relação ao destino.…”
Section: Eficácia Promocional De Destinos Turísticosunclassified
See 1 more Smart Citation
“…It enabled promotion of destination management organizations (DMOs) and tourism operators, such as hotels, tour and travel agents, restaurants and tourism industry networks while sharing information related to tourism product. This topic was intriguing for many researchers from often different viewpoints (Sambhanthan & Good, 2016;Hernández-Méndez & Muñoz-Leiva, 2015;Fatanti & Suyadnya, 2015;Stienmetz et al, 2015;Buhalis & Wagner, 2013;Hays et al, 2012;Saß, 2011) especially when acknowledging the fact that tourism has become an substantial part of the GDP in many countries around the world (Míguez-González & Fernández-Cavia, 2015). Kronenberg et al (2015) conducted a research focused on the effect of advertising on international tourism demand at the destination level and showed that advertising is a significant factor of tourism demand while income and tourism price levels were found less significant.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%